Radical Sympathy: Periodical Circulation and the Peterloo Massacre - Fairclough, Mary (Romanticism and Victorianism on the Net, 2010)
This essay analyses representations of sympathy in radical periodicals in the immediate aftermath of the Peterloo Massacre of August 1819. Recent accounts of the Regency radical press have noted that cheap journals employ a studied language of rational enlightenment in order to counter charges that they provoke unrest. I argue that these periodicals also employ a language of feeling. Through references to the suffering body, radical journals display moral outrage at the atrocity of Peterloo, but they also put the language of feeling to instrumental political use. Using sympathy as a figure for the transmission of riotous emotion within a crowd, these texts signal the physical power of the masses, but significantly, sympathy is also made a model for the processes of distribution through which these texts are diffused throughout the nation. Radical writers exploit the function of sympathy as a physiological process, through which disruption in one part of a body causes instant disruption in another. In a brief moment after Peterloo, the press becomes the circulatory medium through which both national emotional distress and political response can be co-ordinated. My analysis focuses on the often short-lived radical journals produced in the immediate aftermath of Peterloo, The Cap of Liberty, The London Alfred, The White Hat and The Democratic Recorder. I discuss these titles alongside the longer-running Hone’s Reformist Register, The Black Dwarf, The Gorgon, and The Medusa. In signalling the ephemeral and embattled nature of their existence, these journals mark the uncertain distinction between textual diffusion, emotional exchange and physical unrest at this moment of crisis.